2015
DOI: 10.3897/phytokeys.48.4798
|View full text |Cite
|
Sign up to set email alerts
|

Two new species of Indigofera L. (Leguminosae) from the Sneeuberg Centre of Floristic Endemism, Great Escarpment (Eastern and Western Cape, South Africa)

Abstract: Two new species of Indigofera L. (Leguminosae) are described from the Sneeuberg Centre of Floristic Endemism on the southern Great Escarpment, Eastern and Western Cape Provinces, South Africa. Both species are localised high-altitude endemics. Indigofera magnifica Schrire & V.R. Clark is confined to the summit plateau of the Toorberg–Koudeveldberg–Meelberg west of Graaff-Reinet, and complements other western Sneeuberg endemics such as Erica passerinoides (Bolus) E.G.H. Oliv. and Faurea recondita Rourke & V.R. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Relevant taxonomic literature (e.g. Craib (1913) ; Fang and Zheng (1994) ; Sun (2006) ; Gao and Schrire (2009 , 2010 ); Chauhan et al (2013) ; Clark et al (2015) ; Pignal and De Queiroz (2019) ) was consulted. Morphological studies were carried out on dried material under a stereomicroscope (Olympus SZX2, Tokyo, Japan) and measurements were made using a ruler and a metric vernier caliper.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Relevant taxonomic literature (e.g. Craib (1913) ; Fang and Zheng (1994) ; Sun (2006) ; Gao and Schrire (2009 , 2010 ); Chauhan et al (2013) ; Clark et al (2015) ; Pignal and De Queiroz (2019) ) was consulted. Morphological studies were carried out on dried material under a stereomicroscope (Olympus SZX2, Tokyo, Japan) and measurements were made using a ruler and a metric vernier caliper.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Pertinent taxonomic literature (e.g. Fang and Zheng 1994 ; Sun 2006 ; Gao and Schrire 2009 , 2010 ; Chauhan et al 2013 ; Clark et al 2015 ) were extensively consulted. Measurements were carried out under a stereomicroscope (Olympus SZX2, Tokyo, Japan) using a ruler and a metric vernier caliper.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Given that the above conclusions rest on only a single mitochondrial genetic marker, in addition to morphological data, there is an urgent need to add molecular data from nuclear sequences and microsatellite loci to provide further support and resolution to the taxonomic conclusions of the present study. Clark et al (2009Clark et al ( , 2011Clark et al ( , 2015 and Nordenstam et al (2009) identified the Sneeuberg Centre of Floristic Endemism and described new plant species endemic to this centre. The distribution of the newly described O. willani coincides closely with the geographical limits of the Sneeuberg Centre described by Clark et al (2009), but extending into the main Drakensberg (Tiffendell and Giant's Castle) at its eastern limit.…”
Section: Distribution and Biologymentioning
confidence: 99%